IT security level of SMEs in Singapore and Malaysia. - Goh, Eik Lim. (2008)
In this study, we formulated an IT security index and examined the variables affecting the IT security levels of SMEs. Our findings suggest that company size, maturity of web site and intranet, industry type and country of operation have a significant impact on the IT security level of the SMEs.